Phytochemical Screening, Antioxidant Activity, and Cytotoxicity of Ethanol, Ethyl Acetate, and n-Hexane Kluwak (Pangium edule) Extract on MCF-7 Breast Cancer Cells - Abidin, Raniindra Khalisha Soediro; Arsianti, Ade (UI Scholars Hub, 2024)
Introduction: Breast cancer occurs quite high and is one of the main causes of death in Indonesia and the world. Current treatment for cancer is expensive and has varying degrees of success and can cause side effects for patients. Kluwak (Pangium edule), whose reseach is still limited has the potential to be used as an alternative treatment for breast cancer. Methods: Kluwak powder was macerated using three different types of solvents to obtain ethanol extract, ethyl acetate extract and n-hexane kluwak extract. Phytochemical tests and thin layer chromatography (TLC) were carried out to determine the type and amount of phytochemical components of kluwak extract. The antioxidant activity of kluwak extract was tested using the DPPH method and the cytotoxic effect on MCF-7 breast cancer cells was determined using the MTT test. Results: The phytochemical components contained in kluwak extract include flavonoids, alkaloids, triterpenoids and glycosides. The ethanol extract of kluwak showed very weak antioxidant activity (IC50 = 26459 µg/ml), while the antioxidant activity of the ethyl acetate and n-hexane extracts could not be determined. Ethyl acetate and n-hexane kluwak extracts also had a moderate cytotoxic effect on MCF-7 breast cancer cells with IC50 values respectively 132.79 µg/ml and 232.93 µg/ml while the ethanol extract had a weak cytotoxic effect with values IC50 667.91 µg/ml.Conclusion: Kluwak (Pangium edule) extract contains phytochemical compounds and cytotoxic effects on MCF-7 breast cancer cells, so it has the potential to be developed as a therapeutic agent in the management of breast cancer.